The effect on plasma insulin secretion from different amounts of chewing differences in chewing a mouthful for 20 or 40 times . (2017) - Matsuda, Hideto; Uchida, Aya; Hashimoto, Kazuyoshi; Takada, Kazuo
No abstract available